Investigation on the weakness and opportunity of using green building in Tehran by SWOT and PEST with the approach of ANP - Saeed Barat; Amirhossein Hajibabaei (مهندسی و مدیریت ساخت)
Creating the conditions for a good life has always been the goal of mankind. At present, due to the design and inappropriate use of buildings, a lot of energy inputs to these buildings are wasted, which, in addition to destroying the natural resources of the country, also contaminates the air of cities. The purpose of this study was to identify the weaknesses, strengths, opportunities and threats of the green building industry in Iran. For this purpose, by examining the problems surrounding the green building in Iran, the challenges and opportunities of using green buildings using the SWOT and ANP method have been investigated in the research area of ​​Tehran and, finally, the development of appropriate strategies in this The field was dealt with. The results showed that the strategy of controlling and directing government policies in the area of ​​providing facilities for modern building industry worth 0.33 is the first strategy and effective way to improve the green building industry in Iran. Strategies include improving the quality of the construction industry to optimize energy through public facilities, with a value of 0.27, recognizing real costs and using appropriate alternatives, with a value of 0.20, and developing education and culture on the modern green building technology, With a value of 0.16, they are in the forefront. According to the results, the government's policy of providing facilities and tax reductions to reduce costs and enjoy long-term economic benefits will lead to the development of the green building industry in Iran, at the head of the reviewed strategies. In general, the findings of this study indicate that the high cost of green building is considered to be a major barrier to expansion of construction with modern methods, and the reduction of financial affairs around this area through the provision of facilities and discounts will play a significant role in expanding it. .